Do visual attentional factors contribute to phonological ability? Studies in adult dyslexia - Buchholz, J; Aimola Davies, A (Routledge, 2007)
A case study approach was taken to examine the role of visual attention and auditory memory processes in eight adults with dyslexia, all of whom demonstrated phonological difficulties. The participants were administered a battery of neuropsychological tests and participated in an attentional cueing experiment. Individual data revealed that, although one adult with dyslexia showed overt visual attention deficits on a visual search task, and five showed auditory working memory deficits, the difficulty that all of the adults with dyslexia had in common was with covert shifts of attention toward and away from fixation. These results indicate that deficits in overt visual attentional processing and working memory can be present with dyslexia, but neither is a necessary requirement. Overall, the results suggest that covert visual attention makes a significant contribution to phonological ability, which thus has implications for reading ability.